2021
DOI: 10.1155/2021/6615612
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticopleural Fistula as a Rare Cause of Both-Sided Pleural Effusion

Abstract: A pancreaticopleural fistula is a rare cause of pleural effusion. It is a complication of chronic or acute pancreatitis. It is rarely formed to the right or both pleural cavities. Diagnosis and proper treatment often turn out to be difficult and require the cooperation of a multidisciplinary team. The authors present the case of a 59-year-old patient treated for recurrent pleural effusion of unknown origin, first to the left and then to the right pleural cavity. After many months of treatment, the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(22 reference statements)
0
2
0
2
Order By: Relevance
“…32 If pleural effusion occurs on the right side, a pseudocyst of the pancreas or a fistula between the pancre as and the pleura may be involved in its genesis. 33 Pleural effusion has been integrated into several clinical grading scores for predicting SAP, such as the BISAP score, 3 and its volume is considered to be a valid imaging biomarker for assessing the se verity and clinical course of AP. 34,35 In our study, pleural effusion was found to be of great impor tance in the analysis of variable importance in the ANN model (FIGuRE 1), and the SHAP summa ry plot for the XGBoost model showed that it was useful for prediction of SAP (FIGuRE 2).…”
Section: Explanation: Individual Prediction On the Test Samplementioning
confidence: 99%
“…32 If pleural effusion occurs on the right side, a pseudocyst of the pancreas or a fistula between the pancre as and the pleura may be involved in its genesis. 33 Pleural effusion has been integrated into several clinical grading scores for predicting SAP, such as the BISAP score, 3 and its volume is considered to be a valid imaging biomarker for assessing the se verity and clinical course of AP. 34,35 In our study, pleural effusion was found to be of great impor tance in the analysis of variable importance in the ANN model (FIGuRE 1), and the SHAP summa ry plot for the XGBoost model showed that it was useful for prediction of SAP (FIGuRE 2).…”
Section: Explanation: Individual Prediction On the Test Samplementioning
confidence: 99%
“…и распространении свищевого ходи забрюшинно, в направлении грудной клетки могут формироваться панкреатикоплевральные или панкреатикобронхиальные свищи [6][7][8]. Наиболее часто внутренние свищи ПЖ с развитием панкреатогенного асцита или плеврита возникают при хроническом панкреатите, а наружные панкреатические свищи -при остром панкреатите [9].…”
Section: оригинальное исследованиеunclassified
“…Нередко у пациентов наблюдаются и нарушения углеводного обмена. Вместе с легочно-плевральными осложнениями все это обуславливает высокий операционно-анестезиологический риск и может потребовать интенсивной предоперационной подготовки [4,6].…”
Section: оригинальное исследованиеunclassified
“…This form of internal pancreatic fistula is characterized by massive pleural effusion. Treatment options for pancreaticopleural fistula include (i) octreotide and thoracocentesis/thoracostomy, (ii) endoscopic retrograde cholangiopancreatography (ERCP) and stenting together with octreotide, and (iii) surgical management that includes pancreatic resection and enteropancreatic drainage [1][2][3][4][5]. ERCP is expensive and not readily available in developing, resource-poor nations.…”
Section: Introductionmentioning
confidence: 99%